A review of preoperative manoeuvres for prophylaxis of endophthalmitis in intraocular surgery: topical application of antibiotics, disinfectants, or both?. Issue 1 (January 2016) - Grzybowski, Andrzej; Kuklo, Patrycja; Pieczynski, Janusz; Beiko, George
Abstract : Purpose of review: Postoperative endophthalmitis is an ophthalmic surgeon's most feared complication, as it portends a high probability of visual loss. The purpose of this article is to review the literature on the subject of preoperative measures used for prevention of postoperative endophthalmitis and to determine the effectiveness of these measures. Recent findings: The present reviewed literature regarding topical prophylaxis of endophthalmitis in cataract surgery. Summary: There is strong evidence for the use of povidone-iodine preoperatively for prophylaxis of postoperative endophthalmitis in ocular surgery; the evidence for topical antibiotics is not as compelling.